Inflatable Reflector Antenna - Mafalda Ho de Almeida Santos (2021)
SARIA (Synthetic-Aperture Radar using an Inflatable Antenna) is an experiment selected to fly in a stratospheric balloon, in the scope of the REXUS/BEXUS programme cycle 13, and will use an inflatable antenna, operating at 5.8 GHz, to create Synthetic-Aperture Radar (SAR) images. Several problems, such as material selection, have prevented SARIA from developing an operational inflatable antenna. The objective of this dissertation is to design and implement an inflatable parabolic reflector antenna, at 5.8 GHz, with a diameter of 1m as well as to control the inflatable antenna pressure using an active inflation system. This work uses Finite Element Method (FEM) to assist on the initial developing phases of an inflatable antenna. To simulate the inflatable antenna shape, at several differential pressure values, the Finite Element Analysis (FEA) software Abaqus/FEA was chosen. A Matlab script was used to compute the radiation pattern of an inflatable antenna. As a result, it is possible to estimate the optimal differential pressure interval and characterize the Radio Frequency (RF) properties of an inflatable antenna prior to manufacturing. Using these tools, a new design modification for SARIA inflatable antenna is proposed. An inflatable antenna is manufactured by hand using Mylar® for the reflective part and transparent plastic for the canopy. The pressure of this antenna is controlled by an active inflation system which is responsible for keeping the inflatable antenna differential pressure inside an optimal interval. An inflatable antenna with a gain of 23.77 dBi at 5.8 GHz was obtained. Its characterization has revealed a gain loss of 5.6 dBi, in respect to the simulated gain, due to implementation difficulties, namely the manufacturing process, which are explained in the thesis. This work contributes to the expertise of developing inflatable antennas for low pressure applications and in orbital environment applications.